Does portion size matter? Dynamic changes in hedonic and emotional responses to foods varying in portion size - Salazar Cobo, Maria Isabel; Jager, Gerry; de Wijk, René; de Graaf, Cees; Zandstra, Elizabeth H. (Food quality and preference, 2022)
•Large portion sizes of indulgent foods drive overconsumption.•Assessment of hedonic and emotional responses to high energy-dense foods varying in portion size.•Small and regular portions were better liked than the large portions.•Small and regular portions had similar emotional (TDE) profiles with positive emotions, whereas the large portion evoked more negative emotional profiles.•These findings add to identify the ideal portion size of a food for inducing a positive emotional response. One way to promote healthier eating behaviors is to reduce food portion sizes and thereby decrease the average daily energy consumed. Positive emotion is a crucial factor in consumers affective responses to food and add to liking ratings in predicting food preferences and choices. Despite this, we know little about the emotional experiences in response to variations in portion size. This study investigated dynamic changes in hedonic and emotional responses to high energy-dense foods varying in portion size. In a within-subjects design, 58 participants (aged 24.1 ± 2.9 years) randomly consumed three different food portions (i.e., small, regular and large) of two food products (i.e., ice cream and pizza) across six experimental sessions. Explicit measures included liking scores and scores on hunger, arousal, overall satisfaction and Temporal Dominance of Emotions (TDE). Implicit measures included facial (emotional) expressions using FaceReaderTM. Results showed that the small and regular portions scored higher on liking than the large portions, for both the ice cream and pizza. In addition, the small portions had similar emotional (TDE) profiles as the regular portions (happy, relaxed and peace), whereas the large portions evoked more negative emotional (TDE) profiles compared to the small and regular portions (bored, guilty, disgusted). The implicit measure facial expressions resulted in a less clear picture, except for the dimensions valence and arousal for ice cream. Participants showed more negative facial expressions and were more aroused during consumption of the regular and large (too much) portion as compared to the small portion during consumption of ice cream. These findings contribute to a better understanding of the role of emotions in the consumption experience of food products varying in portion size and will help to identify the ideal size of a food product for inducing a positive emotional response.